European Society of Endodontology position statement: The use of CBCT in Endodontics. (June 2014) - Patel, S.; Durack, C.; Abella, F.; Roig, M.; Shemesh, H.; Lambrechts, P.; Lemberg, K.
Abstract This Position Statement represents a consensus of an expert committee convened by the European Society of Endodontology (ESE) on the use of Cone Beam Computed Tomography (CBCT). The statement is based on the current scientific evidence, and provides the clinician with evidence‐based criteria on when to use CBCT in Endodontics. Given the dynamic and changing nature of research, development of new devices and clinical practice relating to CBCT, this Position Statement will be updated within 3 years, or before that time should new evidence become available.